Arthroscopic Treatment of Posttraumatic Elbow Stiffness Due to Soft Tissue Problems. Issue 5 (4th October 2020) - Dai, Junxi; Zhang, Guofeng; Li, Shulin; Xu, Jianguang; Lu, Jiuzhou
Abstract : Objectives: To evaluate the effectiveness of arthroscopic management of posttraumatic elbow stiffness due to soft tissue problems. Methods: A retrospective review of 30 consecutive arthroscopic elbow releases for posttraumatic stiff elbow from November 2011 to December 2019 was conducted. Stiff elbows with bony problems, such as heterotopic ossification, intraarticular nonunion or malunion, and cartilage lesions were excluded from this study. Contracture and adhesion of soft tissue around the elbow were identified. Surgical treatments included arthroscopic capsulectomy, ligaments and muscle release, and ulnar nerve release. The results were evaluated using the Mayo elbow performance score (MEPS) and range of motion of the elbow. Surgery‐related complications were assessed. Results: Patients who underwent arthroscopic release were followed up for between 6 and 35 months, with a mean follow‐up time of 10.1 months. The postoperative elbow ROM was 123.2° ± 19°, which was significantly different compared to the preoperative value of 68° ± 32°. In addition, the MEPS score improved from 71.2 ± 10.3 preoperatively to 93.7 ± 6.6 at the final follow‐up, a mean improvement of 22.5 (range, 0–55; P  < 0.05). Postoperative complications included five cases of prolonged drainage from the portal site, three transient nerve palsies, and one hematoma in the medial elbow. Conclusion: With full recognition by the surgeon of the pathologic changes of the soft tissue around the elbow, arthroscopic release is usually safe and effective for posttraumatic elbow stiffness without symptomatic bony problems. Abstract : The sequence of arthroscopic release of common soft tissue contracture or adhesion around elbow in patients with posttraumatic stiffness without symptomatic bony problem